The Effectiveness Of Developing Social Studies Learning Modules Based On Local Wisdom To Improve Local Cultural Character In Mts Ar Rohman Tegalrejo Students - Marwantika, Sherli Aulia; Harmanto, Harmanto; Kasdi, Aminuddin; Nasution, Nasution (Universitas Negeri Surabaya, 2022)
This article aims to develop social studies learning modules based on local wisdom at MTs Ar Rohman Tegalrejo. The type of research is development research using the Borg and Gall model. The research process was carried out until the stage of perfecting the final product which included a feasibility test from several experts. Testing the results of module development using the Independent Sample T-test. The research was conducted at MTs Ar Rohman Tegalrejo. The researchers' efforts to present social studies learning modules based on local wisdom to support social studies integration by raising the theme of local wisdom around students so as to achieve good character education. Based on the assessment of the material aspect, it gets a score of 82%, the language aspect gets a score of 100%, the learning media aspect gets a score of 93% and expert practitioners score 85.6%. Based on the calculation of the average learning module, it is declared valid and suitable for use in learning. There are differences in the value of learning outcomes and also the character of loving local culture in the experimental class and the control class. Based on the output table of the independent samples test in the equal variances assumed section, it is known that the sig (2-tailed) value is 0.000 <0.05, so as the basis for decision making in the independent sample t test it can be concluded that h0 is rejected and h1 is accepted. This it can be concluded that there is a significant difference between the average student learning outcomes in the experimental group and the control group at MTs Ar Rohman Tegalrejo. Keywords: IPS learning module, Local Wisdom, Character Love Local Culture